Methodology for strategic management of the digital potential of complex economic systems based on the platform concept - Glukhov, V. V.; Babkin, A. V.; Shkarupeta, E. V.; Gileva, T. A.; Pletnev, D. A. (Modernizat͡s︡ii͡a︡, innovat͡s︡ii, razvitie, 2023)
Purpose : the purpose of this article is to form a holistic methodology of digital platform strategizing, based on the methods, rules and postulates of strategic management of complex economic systems using different types of platforms in order to increase the digital potential. Methods : the authors used general scientific methods – the method of synthesis, generalization, content analysis, graphical interpretation of data. During the study, we used a six-step method, as well as the standardized methodology of the independent systematic review of the literature on the basis of the eight-step manual. Results : the author's vision of the methodology of strategic management of the digital potential of economic systems as a multi-level cognitive continuum, which allows to describe the full range of theoretical and practical perspectives of the application of methods, rules and postulates of management of the digital potential of economic systems, has been developed. Six architectural levels of the methodology of strategic management of the digital potential of economic systems are identified. Each architectural level is represented by a set of corresponding patterns: the gnoseological level is based on digital philosophy and digital thinking; the paradigmatic level is represented by the coevolution of three approaches and conceptual domain of digital platform strategizing; the ontological level is represented by the terminological apparatus; the semantic level is represented by the framework of digital platform strategizing and the platform concept; the technological level is represented by strategies of economic systems transformation into bionic, business models of digital strategy and digital behavior patterns; the applied level is represented by the methods for assessing the digital maturity and digital gaps of industrial systems. Conclusions and Relevance : the digital development of complex economic systems entails their transformation into bionic and inverted organizations based on an interdisciplinary platform concept, digital strategizing, digital philosophy, digital thinking, digital technologies and Industry 5.0 solutions, driven by the need to increase digital maturity, develop digital capabilities to maintain existing and/or create additional long-term competitive advantages.